Fertility of cloprostenol-treated dairy cattle inseminated at fixed times - Jainudeen, Mohamed Razeen; Camoens, J. (Veterinary Association Malaysia, 1977)
The conception rate (C.R.) of 50 cycling crossbred dairy cattle lnseminted at 72 and 96 hr. (group 1/) or 72 hr. (group III} after the second of two intramuscular injections of 500 ug Cloprostenol (Estrumate ICI, a synthetic analogue structurally related to PGF2α) given 11 days apart was compared with first service C.R. of 18 untreated controls (group I). The higher C.R. in cloprostenol-treated cows (group II = 56%,' group III = 40%) than in untreated controls (group I = 28%) demonstrates that normal fertility could be expected with cloprosteno! and fixed time insemination. The lower C.R. in untreated animals re-emphasizes the difficulties of oestrous detection for artificial insemination under Malaysian conditions. The possibility now exists in Malaysia for a much greater utilization of valuable sires so that the potential benefits of an artificial insemination programme could be realized.